Hurricane Sandy on New Jersey's Forgotten Shore - Perkiss, Abigail, 1981- (Book collections on Project MUSE., 2022)
"Drawing on nearly seventy oral histories conducted following Hurricane Sandy, this book documents the uneven recovery of the storm along New Jersey's Bayshore: the 115 square miles of coastline from Sandy Hook at the lip of the Atlantic Ocean to South Amboy at the mouth of the Raritan River, New Jersey's forgotten shore"--